SISTEM INFORMASI LAYANAN TRANSAKSI EFATA DESAIN INTERIOR - Tika Pratiwi; Maryam (Universitas Islam Balitar, 2021)
Interior design is the design of the layout and also the design of space in a building. Interior companies must have an information system aimed at customers, for example the company EFATA Interior Design. The previous system view only provided information about interior design, without any basic management in it so it was deemed less effective. Previously, EFATA Interior Design was carried out in person or through other communication media. Problems that arise are errors in data recording and also inefficiency in service rental services. This research aims to build an information system that can serve customer order transactions. This system is useful for making transactions, providing services for making transactions and selecting designs. Research has succeeded in building an information system that can facilitate transaction services in design selection, cost calculations and others. Based on the results of the blackbox examiner the system is running according to its function and the SUS questionnaire test is declared feasible. This system is able to assist users in providing transaction services and providing design information.